A water‐cooled monochromator for the B16 Test beamline at the Diamond Light Source: capabilities and performance characterization. (16th November 2018) - Dolbnya, Igor P.; Sawhney, Kawal J. S.; Scott, Stewart M.; Dent, Andy J.; Cibin, Giannantonio; Preece, Geoff M.; Pedersen, Ulrik K.; Kelly, Jon; Murray, Paul
Abstract : Systematic studies of the performance of a water‐cooled X‐ray monochromator, designed and built for the B16 Test beamline at Diamond Light Source, UK, are presented. Abstract : Systematic studies of the performance of a water‐cooled X‐ray monochromator, designed and built for the B16 Test beamline at the Diamond Light Source, UK, are presented. A technical description of the monochromator is given and the results of commissioning measurements are discussed. Overall, the monochromator satisfies the original specifications well and meets all the major requirements of the versatile beamline. Following its successful implementation on B16, the basic monochromator design has been reproduced and adapted on other Diamond Light Source beamlines, including B18 and B21.